(untitled) (Journal of Scientific Research, 2022)
Gamma irradiation of Gelatin brings important changes in its chemical structure, making it suitable for different applications. The irradiated Gelatin may be subjected to different thermal treatments during these applications. Therefore, temperature-dependent changes in irradiated gelatins are a point of interest. Electron spin resonance (ESR) is vital for detecting free radical processes in irradiated polymers. As such, ESR spectra of temperature-dependent porcine Gelatin with low bloom are recorded, and they are analyzed by computer simulation techniques. Component spectra under different conditions are evaluated by the magnetic parameters employed to simulate the ESR spectra. The results indicate that the spectral shape at 300 K (RT) is stable up to 350 K, and signal intensity begins to decay beyond 350 K. The signal vanished around 355 K, designated as radical decay temperature. Bloch analysis is applied to evaluate activation energy associated with free radical decay, calculated around 35 KJ/mole.